Religion and nationalism in India the case of the Punjab - Deol, Harnik (London Routledge, 2000)
This book is not about class structure or economic variables, except where they impinge on the transition to Sikh nationhood.The hypothesis is that three hitherto unrelated sets of factors account for the evolution of the Sikh community. The first is econ
Keywords: Nationalism-India-Punjab; Religion and politics-India-Punjab